Estimated potassium intake and major adverse cardiovascular events in individuals with type 2 diabetes: a prospective cohort study with trans-ethnic validation - Jian-Jun Liu; Huili Zheng; Sylvia Liu; Tsz Kiu Kwan; Resham L. Gurung; Clara Chan; Janus Lee; Keven Ang; Joe de Keizer; Samy Hadjadj; Pierre-Jean Saulnier; Mary F. F. Chong; et al. (Cardiovascular Diabetology)
Abstract Background Data on the relationship between potassium intake and major cardiovascular events (MACE) in patients with diabetes are scarce. We aim to study the association between estimated potassium intake and risk of MACE in individuals with type 2 diabetes. Methods The discovery cohort consisted of 1572 participants with type 2 diabetes from a secondary hospital. The validation cohort consisted of 1430 participants with diabetes from a multicenter study (Chronic Renal Insufficiency Cohort, CRIC). Potassium intake was estimated from potassium in spot urine using Kawasaki formula and in 24-h urine collection in two cohorts, respectively. The primary outcome was MACE defined as a composite of myocardial infarction, stroke and cardiovascular death. Results During a median of 8.2 years of follow-up, 341 MACE events were identified in discovery cohort. Compared to the lowest tertile, participants with potassium intake in the top tertile had 34% lower risk for MACE after adjustment for cardio-renal risk factors (adjusted hazard ratio, aHR [95% CI], 0.66 [0.49–0.89]). This inverse association was more pronounced in participants with normal or moderately elevated albuminuria as compared to those with severely elevated albuminuria (urine albumin-to-creatinine ratio > 300 mg/g, p for interaction < 0.05). In consistence, a higher potassium intake was independently associated with a lower risk of MACE in CRIC participants with diabetes and moderately elevated albuminuria (aHR 0.61 [0.42–0.90], top vs. lowest tertile). Conclusions A high level potassium intake estimated from urine potassium excretion was independently associated with a low risk of MACE in patients with type 2 diabetes. Increasing potassium intake may be a potential effective strategy for cardiovascular risk reduction beyond controlling traditional risk factors.